IMPLEMENTASI MODEL PROBLEM BASED LEARNING DALAM MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS SISWA SEKOLAH DASAR - Putri Handayani; Haifaturrahmah; Nursina Sari (STKIP Subang, 2026)
This study aims to systematically review various research findings on the implementation of the Problem Based Learning (PBL) model in improving elementary school students’ critical thinking skills. This research employs a Systematic Literature Review (SLR) approach using literature sources from Google Scholar, DOAJ, and Scopus, covering publications from 2014 to 2024. A total of 80 articles were identified, of which 35 met the inclusion criteria for in-depth analysis. The results indicate that PBL consistently enhances students’ critical thinking skills through contextual problem-solving activities, collaborative discussions, and individual reflection. The success of PBL implementation is influenced by teachers’ facilitative roles, students’ readiness, and supportive learning environments. However, challenges such as limited time, facilities, and teachers’ understanding of critical thinking assessment remain significant barriers. This review recommends the development of digital and contextual-based PBL models to strengthen the implementation of the Merdeka Curriculum and foster higher-order thinking skills among elementary school students. Keywords: Problem Based Learning, critical thinking, elementary school, Systematic Literature Review